Persepsi Masyarakat Terhadap Desa Wisata Tegalwaru di Ciampea Bogor - Muhtar Mochamad Solihin; Atikah Rahmah Lubis; Christian Pratama Putra (Politeknik Pembangunan Pertanian Bogor, 2022)
The existence of the Tegalwaru Business Tourism Area (KWBT) is a business innovation that has been the development of the community's Small and Medium Enterprises (SMEs) strategy that has existed for a long time. The existence of a business innovation that is a source of additional income for the community that should make the community support it by participating in advancing Tegalwaru Village as a village center for SMEs in Bogor. The aims of this study are 1) to describe the people of Tegalwaru Village, 2) to explain the community's perception of the Tegalwaru Tourism Village, 3) to analyze the factors related to the community's perception of the Tegalwaru Tourism Village. The research approach uses quantitative with the census method. Methods of data collection by distributing questionnaires, interviews and observations. Data analysis used descriptive and inferential analysis (Spearman rank correlation). The results of the study show that: 1) the majority of the people of Tegalwaru Village are in the adult category (40-60 years), the average education of the respondents is in the middle group, namely between SMA-S1, and the income of SME owners in collaboration with KWBT have an income of more than IDR 2,500,000 per month; 2) the result of calculating the average score of 27 means that the perception of SME owners is positive towards the existence of KWBT, 3) factors related to public perception of KWBT are the choice of information, sources of information, relative advantage and level of adjustment.